The theoretical framework of the Artificial Intelligence (AI) challenges in the jewellery industry - Husni, Ainatul; Kaspin, Saadiah (College of Creative Arts, 2025)
Jewellery design is both an artistic and technical practice, combining craftsmanship, creativity, and cultural expression. Rooted in traditional techniques such as stone setting and metallurgy, it continues to evolve through contemporary styles while balancing functionality, aesthetics, and identity. Recent advancements in artificial intelligence (AI) have introduced new opportunities in this field, particularly as a coassistant in concept exploration, storytelling, and experimentation. Generative AI enables efficiency in the early stages of design by transforming sketches into 2D or 3D renderings, accelerating decision- making, and supporting cultural translation. However, current research on AI in jewellery design remains limited, with a predominant focus on technological applications and little attention to emotional, ethical, or cultural dimensions. Examining how the incorporation of AI impacts authenticity, professionalism, and heritage in jewellery creation, requires interdisciplinary and regionally informed research to ensure responsible adoption. Ultimately, while AI enhances creativity and efficiency, the human touch remains indispensable for imparting jewellery with cultural meaning, emotional value, and identity.